Sales Volume and Sales Space Correlation in a Retail Store - Lahrache, Anass; Benkaraache, Taoufik (International Journal of Engineering and Technology, 2019)
In a retailer chain, the allocated sales space for an article or a range is a decision that needs deep reflection due to the commercial implication. Even though, in most of the cases this decision is made on an empirical base. In this paper, we will study this link by defining its nature, its limits and try to understand the potential impact of changing space on the sales and prove the importance of theoretical approach which remained so far on an experimental levelÂ Â Â